Development of an Arduino Uno-Based Harmonic Vibration Demonstration Tool to Enhance High School Students’ Understanding of Physics Concepts - Riva Enjel Simanjuntak; Dedy Hamdani; Bodi Gunawan (Journal of Educational Sciences, 2026)
This study was motivated by students’ low conceptual understanding of harmonic oscillation due to abstract teaching methods and the limited use of experimental tools. This study aimed to develop an Arduino-based teaching aid, evaluate its feasibility through expert validation, measure improvements in students’ conceptual understanding, and examine students’ responses to its use. Unlike conventional teaching aids, the developed Arduino-based system integrates real-time measurement and automatic visualization of multiple harmonic vibration parameters, enabling students to observe and analyze oscillation phenomena more interactively and concretely. The Research and Development (R&D) method was applied using the ADDIE model. The results showed that the teaching aid achieved an average feasibility score of 93%, categorized as highly feasible. Testing on 30 eleventh-grade students using a pretest-posttest design indicated an improvement in conceptual understanding with an N-gain value of 0.76 (high category). Student responses reached an average percentage of 89%, categorized as very good. Thus, the teaching aid is considered suitable for use, effective in enhancing conceptual understanding, and positively received in the learning process. These findings indicate that the Arduino-based teaching aid can be implemented as an interactive experimental medium in physics learning to help students understand harmonic oscillation concepts more concretely, actively, and meaningfully.